2019
DOI: 10.5114/aoms.2019.87686
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TP73-AS1 predicts poor prognosis and regulates cell proliferation and migration in cervical cancer

Abstract: Introduction: Cervical cancer is one of the most common malignant tumors in women, which seriously affects women's health, especially in developing countries. This study aims to investigate novel molecular markers for poor prognosis of cervical cancer to achieve correct guidance of clinical treatment, accurate assessment of prognosis, and provide a new basis for the choice of reasonable treatment options for cervical cancer patients. Material and methods: QRT-PCR was employed to investigate the expression of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Long ncRNAs were previously considered as redundant by-products of RNA polymerase II transcription but many studies have revealed that they are involved in a number of regulatory processes including somatic tissue differentiation and tumor development [6][7][8][9][10]. Recently, many studies have focused on the role of long ncRNA in cancer development and metastasis [11,12]. Our current work was designed to investigate the role of growth-associated long ncRNA 1 (GASL1).…”
Section: Introductionmentioning
confidence: 99%
“…Long ncRNAs were previously considered as redundant by-products of RNA polymerase II transcription but many studies have revealed that they are involved in a number of regulatory processes including somatic tissue differentiation and tumor development [6][7][8][9][10]. Recently, many studies have focused on the role of long ncRNA in cancer development and metastasis [11,12]. Our current work was designed to investigate the role of growth-associated long ncRNA 1 (GASL1).…”
Section: Introductionmentioning
confidence: 99%